A diachronic perspective on lithic raw material procurement strategies and mobility: case studies from the Final Palaeolithic, Mesolithic and Neolithic in Central Europe. Issue 4 (1st January 2022) - Gehlen, Birgit; Affolter, Jehanne; Schön, Werner; Scharl, Silviane; Siegmund, Frank; Fischer, Anna-Leena; Grunert, Mareike; Meiborg, Christa; Mischka, Doris; Treude, Elke; Uthmeier, Thorsten
ABSTRACT: Analysis of prehistoric lithic artefacts helps to answer a wide array of questions concerning archaeological contexts and prehistoric human behaviour. During three projects, we studied the origin of the raw materials of 32 inventories from the Late Glacial and Early Holocene in northwest and southern Germany. The basal petrographic analysis was conducted by the geologist and petro-archaeologist Jehanne Affolter. In addition, data of more than 60 published assemblages from Switzerland as well as western and southern Germany were recorded. The origin of lithic raw materials from most of these inventories was determined using the microfacial method. GIS-based maps of the raw material sources from the aforementioned regions are compiled and raw material catchment areas of the Stone Age sites are mapped. The area calculations of the raw material catchments revealed a diachronic alternation of larger and smaller areas, which above all suggest culturally determined cycles in the range of mobility and communication networks.